1998
DOI: 10.1111/j.1540-8159.1998.tb01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological Examination of the Topography of the Atrioventricular Nodal Artery within the Triangle of Koch

Abstract: 1) in 20% of examined hearts the AVN artery lay just beneath the endocardium near the coronary sinus ostium 2) there is a risk of the AVN artery coagulation during radiofrequency ablation in the slow pathway region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Proximity to these structures may increase the risk of producing block during ablation around, or inside, the ori ce of the coronary sinus, not only for patients with AV nodal reentry tachycardia, but also for those with accessory pathways located in the inferior pyramidal space. Similar relations between the ori ce of the coronary sinus and the nodal artery were observed by Kozluk et al, 1 2 who found arrangements that were potentially at risk in 8% of their 54 patients studied using coronary angiography, and were reported in 20% of the 50 hearts analyzed histologically by Kozlowski et al 9 Despite this, the induction of AV block is rare. This is possibly due to the cooling effect of the normal blood ow together with the brous adventitia that protects the arteries in these regions.…”
Section: Radiofrequency Catheter Ablation and Injury Of The Nodal Arterysupporting
confidence: 70%
“…Proximity to these structures may increase the risk of producing block during ablation around, or inside, the ori ce of the coronary sinus, not only for patients with AV nodal reentry tachycardia, but also for those with accessory pathways located in the inferior pyramidal space. Similar relations between the ori ce of the coronary sinus and the nodal artery were observed by Kozluk et al, 1 2 who found arrangements that were potentially at risk in 8% of their 54 patients studied using coronary angiography, and were reported in 20% of the 50 hearts analyzed histologically by Kozlowski et al 9 Despite this, the induction of AV block is rare. This is possibly due to the cooling effect of the normal blood ow together with the brous adventitia that protects the arteries in these regions.…”
Section: Radiofrequency Catheter Ablation and Injury Of The Nodal Arterysupporting
confidence: 70%
“…, , ). This anatomy implies a possible risk of injuring the atrioventricular nodal artery during slow pathway modification (Dean et al, ; Kozlowski et al, ).…”
Section: Three‐dimensional Image Of the Inferior Pyramidal Spacementioning
confidence: 99%
“…In this group of patients, the terms tachycardia-induced ST-segment depression, myocardial subendocardial ischemia, recording artifact, and other ill-defined terms are used to explain these ECG changes. [ 3 5 ] These ST segment alterations may occur in the presence of various types of artifacts that overlap with the individual components of the QRS complex, which alter the baseline and imitate the typical electrocardiographic changes seen in myocardial ischemia. [ 6 ] An example of such changes is atrial flutter in the inferior leads, in which the flutter wave can imitate pathological q waves and resemble a previous myocardial infarction, but may also affect the ST segment and T waves, mimicking acute ischemic changes.…”
Section: Introductionmentioning
confidence: 99%